Avaliação do desempenho de camada protetora em concreto submetido a meio quimicamente agressivo - Julio Gomes do Val (2007)
This work has as objective evaluates the performance of a concrete with epoxy protection submitted to acid aggressive environment. A concrete was produced with 35MPa, water-cement ratio of 0,50 and polifunccional addictive. The performance of the epoxy ink, it was evaluated through the comparison between a protected concrete and a concrete without protection, before and after they were submitted to different aggressiveness degrees. Tests of concrete strength compression and water absorption, by immersion of specimens, were made, and, also, the concrete mass losses, owned to sulfuric acid chemical attack, in concentrations of 2,5 and 3,0%, were evaluated. The results demonstrate that concretes without protection, submitted to attack, had a loss of resistance larger than 22% and that, with the protection, the resistance loss was smaller. In what refers to the absorption, the variation was of 6,6%, for the concrete without protection, to 2,1%, for the concrete with protection. The mass losses show that for the concrete without protection the loss is of the order of 4,3%, while, for the protected concrete, it is of 2,1%. Besides the conventional attack, for immersion in sulfuric acid, it was made an attack being inserted immersion and dryness of the specimens, which caused deterioration considerably to the concrete larger than the first. Also in this second situation, the use of the protection reduced the impact of the contact with the acid. The research allows to prove the efficiency of epoxy protection in concretes submitted to different aggressiveness degrees.